STUDENTS’ RESPONSES TO THE LECTURER QUESTIONS OF FIFTH SEMESTER STUDENTS’ OF ENGLISH EDUCATION IN MUHAMMADIYAH UNIVERSITY OF BENGKULU - Yosi Marita (Edu-Ling: Journal of English Education and Linguistics, 2017)
ABSTRACT The research was aimed to analyze the students’ responses to the lecturer’s questions. The subject of the research was all of students of the fourth semester of English Deparment of Muhammadiyah University of Bengkulu in the Academic Year 2009/2010. The total of students are 110 students. The reseacher observed five lectures, they were: Writing II, Curriculum and Material Development, Speaking IV by, Language Testing, and Grammar IV. Three were 34 items that consist of three types of responses whether there were oral, written and non-verbal. The result of the analysis show that the students responses; eye contact (42%:often), it can be concluded that the response dominantly was eye contact response. Besed on the result, the researcher suggests as follows: (1) the students are hoped to be braver and confidence to speak up to the lecturers in responding to the lecturers’ questions. (2) for the lecturers of Muhammadiyah University of Bengkulu, make the classroom atmosphere more interactive among the lecturers and the students by giving the support and motivation to the students to practice their English.